The Effectiveness of Bureaucratic Reform in Realizing Good Governance and Public Services - Marsha Medina Zhabilla; Ni'ma Trirahayu Budiyanto (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze and evaluate the effectiveness of bureaucratic reform in realizing good governance and improving the quality of public services in Indonesia. The research employs a library research method by reviewing various relevant academic sources, including journals, books, and official reports. The findings indicate that bureaucratic reform has a positive impact on enhancing efficiency, effectiveness, transparency, and accountability in public administration. The implementation of reforms through service digitalization, procedural simplification, and the application of standard operating procedures (SOPs) has significantly improved the quality of public services, particularly in terms of speed, accessibility, and service certainty. Furthermore, bureaucratic reform promotes the implementation of good governance principles, such as transparency, participation, and accountability. However, several challenges remain, including resistance to change, limited human resource competencies, and uneven policy implementation across government institutions. Therefore, continuous efforts are required through capacity building, strengthening monitoring systems, and optimizing the use of information technology to ensure the sustainability and success of bureaucratic reform.